PCI effects and the gradual formation of Rydberg series due to photoelectron recapture, in the Auger satellite lines upon Xe 4d−15/2 photoionization. (17th April 2015) - Kosugi, Satoshi; Iizawa, Masatomi; Kawarai, Yu; Kuriyama, Yosuke; David Kilcoyne, A L; Koike, Fumihiro; Kuze, Nobuhiko; Slaughter, Daniel S; Azuma, Yoshiro
Abstract: The Xe (N5 O2, 3 O2, 3 ) Auger electron spectra originating from 4d −1 5/2 inner-shell photoionization were measured, with photon energy tuned close to the ionization threshold. As the photon energy approaches the threshold from above the 4d −1 5/2 photoionization threshold, Rydberg series structures are formed within the Auger electron peak by the recapture of the photoelectron into high-lying ion orbitals. They emerge in the tail on the higher energy side of the post–collision interaction (PCI) profile of the Auger electron. Discrete Rydberg peaks replace the continuous PCI tail and gradually form a series with intensity distribution emulating the intensity profile of the continuous tail. Structures due to the Xe + 5p 4 ( 1 S0, 1 D2, 3 P2, 1, 0 ) m l series were observed and assigned.